2021
DOI: 10.1177/08971900211064154
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Barriers to Communication Between Pharmacists During Transitions of Care

Abstract: Background Effective communication between pharmacists across healthcare settings is essential to facilitate transitions of care (TOC) and improve patient outcomes. Objective To explore pharmacists’ communication methods and preferences and identify barriers to communication during TOC. Methods A survey was distributed to a convenience sample of pharmacists in California, Connecticut, Illinois, Massachusetts, New Jersey, and Texas. The survey collected information on pharmacists’ demographics, practice setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The findings from this work also highlight barriers that may be more global to CMM and ToC. For example, several other studies examining ToC have found similar barriers, such as identifying high‐risk patients, staffing shortages, and information management and transfer between organizations 21–25 . In fact, in one study examining implementation of transitional care services across 22 healthcare organizations, the authors found that a major barrier was inadequate medication review, reconciliation, and education during ToC and several sites reported suboptimal integration of pharmacy services further limiting medication management 25 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The findings from this work also highlight barriers that may be more global to CMM and ToC. For example, several other studies examining ToC have found similar barriers, such as identifying high‐risk patients, staffing shortages, and information management and transfer between organizations 21–25 . In fact, in one study examining implementation of transitional care services across 22 healthcare organizations, the authors found that a major barrier was inadequate medication review, reconciliation, and education during ToC and several sites reported suboptimal integration of pharmacy services further limiting medication management 25 .…”
Section: Discussionmentioning
confidence: 52%
“…For example, several other studies examining ToC have found similar barriers, such as identifying highrisk patients, staffing shortages, and information management and transfer between organizations. [21][22][23][24][25] In fact, in one study examining implementation of transitional care services across 22 healthcare organizations, the authors found that a major barrier was inadequate medication review, reconciliation, and education during ToC and several sites reported suboptimal integration of pharmacy services further limiting medication management. 25 Clearly, there is a need for CMM services during ToC, 26 and the participants in this project spoke of the value CMM brings to patient care and optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes evidence showing methods for improved collaboration that are sustainable and financially viable 12,15,30,31,38–45 . It is important to acknowledge that the growth and development of pharmacist‐to‐pharmacist collaborative practices in these early stages contribute to the heterogeneity of outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…37 Table 1 summarizes evidence showing methods for improved collaboration that are sustainable and financially viable. 12,15,30,31,[38][39][40][41][42][43][44][45] It is important to acknowledge that the growth and development of pharmacist-to-pharmacist collaborative practices in these early stages contribute to the heterogeneity of outcomes. Clinicians and teams of collaborators can look to guidance documents/tools for proposed quality metrics to guide future design for alignment around key outcomes.…”
Section: Discussionmentioning
confidence: 99%